Mathematical Resilience and Motivation to Study in Mathematically Gifted Students - Self-Determination Approach - Knopik, Tomasz; Oszwa, Urszula (Przegląd Badań Edukacyjnych (Educational Studies Review), 2023)
Aim. This study aims to analyse the relationship between mathematical resilience (MR) and motivation (MOT) of mathematically gifted students (MG) through the lens of the self-determination theory (SDT). Questions. Based on a review of the results of previous research, the current study sought answers to four research questions revolving around the relationship between MR and MOT, the predictors of high mathematical achievement, the level and differentiations of dimensions of MR, and the types of MOT in a group of Polish MG high school students aged 16-18 (n = 113). The results of MG group were compared to a comparison group (n = 121). Method. The Mathematical Resilience Scale (MRS-24) and the Motivation to Learn Questionnaire (MLQ-30) were used to measure MR and MOT. Correlation analyses between indicators of the variables, regression analysis and statistical intergroup comparisons were conducted as well. Results. Significant correlations were found between MR and MOT in the MG group. The strongest predictors of high mathematical achievement in the MG appeared to be the students’ beliefs regarding the value of mathematics, along with their overall level of MOT to learn. The level of MR was elevated in the MG and was observed to be significantly higher compared to that in the comparison group. The dimension analysis of MR indicated the particular importance of the perceived values of mathematics as the leading factor in this variable that most strongly differentiated the two groups. The analysis of MOT types in the MG depicted that they manifested mainly intrinsic MOT, identification and introjection, and the level of indicators of these three types of MOT distinguished in the SDT was significantly higher in this group than those in the comparison group. Conclusion. As indicated by the study, the promotion of the social value of mathematics is crucial in shaping students’ MR and MOT as efficient problem-solving tools in school and daily life.